Post-load insulin resistance is an independent predictor of hepatic fibrosis in virus C chronic hepatitis and in non-alcoholic fatty liver disease. Issue 9 (28th March 2007) - Svegliati-Baroni, G; Bugianesi, E; Bouserhal, T; Marini, F; Ridolfi, F; Tarsetti, F; Ancarani, F; Petrelli, E; Peruzzi, E; Cascio, M Lo; Rizzetto, M; Marchesini, G; et al.
Abstract : Background: Insulin resistance is a significant risk factor for hepatic fibrosis in patients with both non-alcoholic fatty liver disease (NAFLD) and chronic hepatitis C (CHC), either directly or by favouring hepatic steatosis. Several methods are available to assess insulin resistance, but their impact on this issue has never been evaluated. Aims: To determine the relative contribution of steatosis, metabolic abnormalities and insulin resistance, measured by different basal and post-load parameters, to hepatic fibrosis in CHC and in NAFLD patients. Methods: In 90 patients with CHC and 90 pair-matched patients with NAFLD, the degree of basal insulin resistance (by the homeostasis model assessment, (HOMA)) and post-load insulin sensitivity (by the oral glucose insulin sensitivity (OGIS) index) was assessed, together with the features of the metabolic syndrome according to Adult Treatment Panel III definition. Data were correlated with hepatic histopathology. Results: The prevalence of basal insulin resistance (HOMA values >75th percentile of normal) was 23.3% in CHC patients and 57.8% in NAFLD, but it increased to 28.8 and 67.8% when measured by post-load insulin resistance (OGIS <25th percentile). In a multivariate model, after adjustment for age, gender and body mass index, OGIS was a predictor of severe fibrosis in CHC and in NAFLD patients, independently of steatosis. An OGIS value below the cut-off of the 25th percentile increased the likelihood ratio of severe fibrosis by a factor of 1.5–2 and proved to be a more sensitive and generally more specific test than HOMA-R for the identification of subjects with severe fibrosis both in NAFLD and in CHC. Conclusions: Post-load insulin resistance (OGIS <9.8 mg/kg/min) is associated with severe hepatic fibrosis in both NAFLD and CHC patients, and may help identify subjects at risk of progressive disease.